(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Family relations amid the COVID-19 pandemic have greatly impacted many individuals’ health. Many families faced challenges caused by the COVID-19 pandemic, like financial instability, anxiety, stress, and health problems. Still, many families are getting closer to each other during the pandemic. The impingement of family relations amid the COVID-19 pandemic on the mental health of selected graduating students tends to investigate the impact of family during the pandemic on respondents’ mental health. The respondents in the study are Three Hundred Forty-Seven (347) selected graduating students of Bestlink College of the Philippines, and the researchers conducted a survey questionnaire through the online platform Google form to determine the data and analyze and interpret it. The results of the study are the respondents’ level of family relations amid the COVID-19 pandemic has a high impact on the mental health of selected graduating students based on stated variables, and the majority of the respondents as to age 22 years old have a frequency of 114 or 33 percent. This concludes that there are improvements in family relations during the COVID-19 pandemic to students’ mental health. These are parenting style, attitude and bonding. The respondents are financially unstable and have difficulty coping with their studies. It shows that family plays an important role in one’s individual that matters to their mental health, especially in those times of pandemic. The recommendation that the researcher received is that Parents should learn how to connect with their children to provide the absence of emotional needs.